Co-op advertising models in one manufacturer-two retailers supply chains with spillover effect. (2016) - Zhang, Hong; Zhang, Quan-ju
In the literature of cooperative advertising (co-op), many researchers paid their attentions on the situation of one manufacturer and one retailer. This paper expands the research to one manufacturer and two retailers. The effect of co-op advertising mechanism is discussed here through national advertising investment, local advertising expenditure, and spillover effect which reveals the influence that one retailer's local advertising effort exerts on the others' sales. For this purpose, three co-op advertising models are discussed: one non-cooperation game, one horizontal cooperation game and one vertical cooperation game. Comparing the three models, we can draw three significant conclusions as follows. First, under the condition of the manufacturer taking a non-cooperative attitude, retailers who cooperate with each other are willing to make more local advertising effort than the non-cooperative ones in the growth period of the product, but in the maturity period, the opposite is the case. In the second, the manufacturer's national advertising investment and the spillover effect are uncorrelated. Also, it can be guaranteed that the national advertising investment is greater than the other two models in vertical model. In the third vertical model, the higher the co-op advertising reimbursement portion is, the more the retailers' profit, and the less the manufacturer's profit. The system's profit and the reimbursement policy are uncorrelated